Perancangan Sistem Informasi Kepegawaian sebagai Pendukung Keputusan Daftar Urut Kepangkatan di Universitas Sebelas Maret dengan Metode RAD - Retno Wulan Damayanti; Muh. Hisjam; Haryono Setiadi (Industrial Engineering Study Program, Faculty of Engineering, Universitas Sebelas Maret, 2008)
Compilation of Daftar Urut Kepangkatan (DUK) is one of the routine duty in human resource unit of Sebelas Maret University (UNS). Variable which must be paid attention in compilation of DUK are position, year of service, occupation practice, education and age. The change in structural PNS is very dynamic, so that DUK’s renewal done every months. Existence of some variable which must be paid attention in compilation of DUK and also the change in structural PNS UNS, hence needed of integrated information system so that DUK is up to date and valid. One of the information system development method by paying attention and desire requirement of consumer is Rapid Application Development (RAD). RAD method use approach of prototyping. Using this method, design of information system will be focused at desire requirement of human resource unit UNS.